Bristol Deaf Memories: archives, nostalgia and the loss of community space in the deaf community in Bristol. (2nd September 2019) - O'Brien, Dai; Stead, Lisa; Nourse, Nicholas
Abstract: The deaf community in the UK has undergone major changes in recent years, which has uprooted it from its traditional foundations, the deaf club and deaf residential school. This article examines the effect of the closure of the deaf club in Bristol, a city in the South West of England, which resulted in the loss of an important community place and spaces for deaf people in the city. We discuss, with a strong focus on methodology, a community event celebrating Bristol's deaf heritage organised by the research team which utilised archive materials, including archived actuality footage. This article draws on interview data elicited from participants in that event to explore the meanings connected to space and place in both past and present by the deaf community in Bristol. Concepts of the rhizome and the smooth and striated spaces of Deleuze and Guattari were found to be useful models with which to engage with the contemporary struggles of the deaf community for community recognition and organisation. We also suggest an online mapping application which enables the practice of rhizomatic cartography could be a way forward in preserving the deaf heritage and history of the city.